Primary Leiomyosarcoma of Gallbladder: A Rare Diagnosis - Ajay Savlania; Arunanshu Behera; Kim Vaiphei; Harjeet Singh; R. K. Dhiman; Ajay Duseja; Y. K. Chawla (Case Reports in Gastrointestinal Medicine)
Leiomyosarcoma of the gallbladder is a rare entity, constituting about 1.4 per 1000 gallbladder malignancies. Literature review shows female preponderance in sixth decade of life, due to unknown reasons. We report one such rare case of a 50-year-old female admitted with pain in right upper abdomen. On examination, mass was felt in right hypochondrium. The ultrasound abdomen showed mass with loss of interface with liver and cholelithiasis. CECT abdomen showed polypoidal gallbladder malignancy with ill-defined interface with liver. She was operated upon with diagnosis of carcinoma gallbladder; extended cholecystectomy was done. Histopathological examination revealed spindle-cell proliferation and possibility of malignant tumor of mesenchymal origin was kept. This was later confirmed on immunohistochemistry.